2010
DOI: 10.1177/097168581001600203
|View full text |Cite
|
Sign up to set email alerts
|

Individual Spirituality at Work and Its Relationship with Job Satisfaction, Propensity to Leave and Job Commitment

Abstract: Spirituality is a hot topic of research in recent times in management arena. Though the organizational researchers have intensely started exploring this area, the studies related to selling organizations are few, and fewer are the studies related to selling organizations with individual (sales professional) as the unit of theory. The present study explores the relationship between ‘individual spirituality at work’ and sales professionals’ ‘job satisfaction’, ‘propensity to leave’ and ‘job commitment’. This wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 22 publications
5
80
1
5
Order By: Relevance
“…However, when POP was tested as a moderator in the relationship between WPS and two employee attitude variables, significant and marginally significant interaction effects provided partial support for the third hypothesis, which suggests that employees' perceptions of organizational politics shaped the relationships between WPS and employee attitudes. This study confirmed the findings of previous studies (e.g., Chawla & Guda, 2010;Kinjerski & Skrypnek, 2008;Usman & Danush, 2010;Van der Walt & de Klerk, 2014) that WPS positively influences job satisfaction. However, it should be noted that these studies used WPS scales that have different dimensions (mainly sense of community at work, alignment with organization's values, and meaningful work).…”
Section: Discussionsupporting
confidence: 92%
“…However, when POP was tested as a moderator in the relationship between WPS and two employee attitude variables, significant and marginally significant interaction effects provided partial support for the third hypothesis, which suggests that employees' perceptions of organizational politics shaped the relationships between WPS and employee attitudes. This study confirmed the findings of previous studies (e.g., Chawla & Guda, 2010;Kinjerski & Skrypnek, 2008;Usman & Danush, 2010;Van der Walt & de Klerk, 2014) that WPS positively influences job satisfaction. However, it should be noted that these studies used WPS scales that have different dimensions (mainly sense of community at work, alignment with organization's values, and meaningful work).…”
Section: Discussionsupporting
confidence: 92%
“…An earlier study conducted by Milliman et al (2003) among part-time employees revealed significant positive relationships between certain dimensions of spirituality and job satisfaction. Later, other studies have also shown that in organizations where spirituality is respected, employees experience greater job satisfaction (Pawar, 2009;Chawla & Guda, 2010;Altaf & Awan, 2011;Lazar, 2010). Hence, employees whose spiritual needs are fulfilled tend to be more satisfied with their jobs.…”
Section: Relationship Between Workplace Spirituality and Job Satisfacmentioning
confidence: 93%
“…The relationship between workplace spirituality and its outcomes has also been well documented. Previous empirical research has revealed a positive relationship between workplace spirituality and job satisfaction (Chawla & Guda, 2010;Milliman et al, 2003), organizational performance (Neck & Milliman, 1994) and organizational commitment (Chawla & Guda, 2010;Milliman et al, 2003) and a negative relationship with the intention to quit (Chawla & Guda, 2010).…”
Section: Alignment Of Valuesmentioning
confidence: 99%